Experimental Study on the High-Temperature and Low-Temperature Performance of Polyphosphoric Acid/Styrene-Butadiene-Styrene Composite-Modified Asphalt - Xueqian Li; Jianzhong Pei; Jiujian Shen; Rui Li (Advances in Materials Science and Engineering)
The high-performance asphalt materials are used to replace the ordinary road asphalt that cannot meet the requirements of natural environment and traffic situation, which is the effective way to solve poor asphalt pavement durability. In this paper, polyphosphoric acid- (PPA-) modified asphalt and polyphosphoric acid (PPA)/styrene-butadiene-styrene (SBS) composite-modified asphalt with different PPA content were prepared by using two-type asphalt. The effect of PPA modifier on asphalt was analyzed by using the creep elastic recovery rate, accumulating strain and creep modulus tests. The results showed that asphalt types and the PPA could significantly improve the elastic recovery rate of asphalt, reduce the cumulative strain and creep stiffness of the viscosity part, improve the high-temperature performance, and reduce the permanent deformation of the asphalt under repeated load. The high-temperature performance and low-temperature performance of PPA-modified asphalt were studied by the chemical and physical modification techniques. The advantages of modified asphalt are well developed while reducing the price of it, which has important technical and economic significance.